In situ examination of Lactobacillus brevis after exposure to an oxidizing disinfectant - Zhao, Yu; Knøchel, Susanne; Siegumfeldt, Henrik (Frontiers in Microbiology, 2014)
Beer is a hostile environment for most microorganisms, but some lactic acid bacteria can grow in this environment. This is primarily because these organisms have developed the ability to grow in the presence of hops. It has been speculated that hop resistance is inversely correlated to resistance against oxidation, and this would have great impact on the use of various disinfectants in the brewing industry. In this study, we cultivated bacteria under aerobic and anaerobic conditions, and then investigated the in situ outgrowth of individual cells into microcolonies on MRS agar after exposure to the oxidizing agent peracetic acid (PAA). An automated microscope stage allowed us to analyse a much larger number of cells over extended periods of incubation. After PAA treatment, the lag time increased markedly, and extensive variation in morphology, µmax as well as stress resistance was observed between and within the tested L. brevis strains. The results suggest that aerobic cultivation increased the oxidative stress tolerance in L. brevis. The results also show that dead cells are randomly distributed in a microcolony and the majority of non-growing individual cells do not stain with a membrane impermanent dye (Propidium iodide), which indicates that PAA may not destroy the plasma membrane. In conclusion, the developed microscopic analysis of individual cells on MRS agar can provides faster results and more details of cell physiology compared to the traditional CFU method.